Effects of 1p/19q Codeletion on Immune Phenotype in Low Grade Glioma - Lv, Lei; Zhang, Yuliu; Zhao, Yujia; Wei, Qinqin; Zhao, Ye; Yi, Qiyi (Frontiers in Cellular Neuroscience, 2021)
Background: Chromosome 1p/19q codeletion is one of the most important genetic alterations for low grade gliomas (LGGs), and patients with 1p/19q codeletion have significantly prolonged survival when compared with those without the codeletion. And tumor immune microenvironment also plays key roles in the tumor progression and prognosis. However, the effect of 1p/19q codeletion on tumor immune microenvironment in LGGs was unclear. Methods: Immune cell infiltration of 281 LGGs from The Cancer Genome Atlas (TCGA) and 543 LGGs from Chinese Glioma Genome Atlas (CGGA) were analyzed for immune cell infiltration through three bioinformatics tools: ESTIMATE algorithm, TIMER and xCell. The infiltrating level of immune cells and expression of immune checkpoint genes were compared among different subgroups classified by 1p/19q codeletion and IDH mutation status. The differential biological processes and signaling pathways were evaluated through Gene Set Enrichment Analysis (GSEA). The correlations between variables were analyzed using Spearman correlation analysis. Results: 1p/19q codeletion was associated with immune related biological processes in LGGs. Infiltrating level of multiple kinds of immune cells, such as B cells, dendritic cells, and macrophage, and expression of immune checkpoint genes, such as PD-L1, PD-L2 and TIM3, were significantly lower in 1p/19q codeletion LGGs compared to 1p/19q noncodeletion cohorts. There were 127 immune related genes on chromosome 1p or 19q, such as TGFB1, JAK1 and CSF1. The expression of these genes positively correlated with their DNA copy number mostly. These genes are distributed in multiple immune categories, such as chemokines/cytokines, TGF-β family member and TNF family members, which could regulate immune cell infiltration and expression of the immune checkpoint genes in tumor. Conclusions: Our results indicated that 1p/19q codeletion status is closely associated with the immune microenvironment in LGGs. LGGs with 1p/19q codeletion display a less immune cell infiltration and lower expression of immune checkpoint genes than 1p/19q noncodeletion cases. Mechanistically this may be at least in part due to deletion of copy number of immune related genes in LGGs with 1p/19q codeletion. Our findings may be relevant to investigate immune evasion in LGGs and contribute to the design of immunotherapeutic strategies for patients with LGGs.